Computation of Revan Topological Indices for Phenol-Formaldehyde Resin. (27th April 2022) - Kamran, Muhammad; Salamat, Nadeem; Hussain Khan, Riaz; Abaid Ullah, Muhammad; Hameed, Muhammad Shazib; Pandit, M. K.
Abstract : Phenol-formaldehyde resin has a wide range of moldings. The phenolic resin retains properties at the freezing point; hence, it is difficult to determine its age. However, it has immense consumption in manufacturing electrical equipment due to its insulating property. There are many types of topological indices such as degree-based topological indices, distance-based topological indices, etc. Topological indices correlate some physiochemical properties of chemical compounds. In this article, the degree-based topological indices of phenol-formaldehyde resin have been determined. Furthermore, the Revan index, hyper Revan index, modified Revan index, sum connectivity Revan index, harmonic Revan index, and inverse Revan index have been calculated.